Dampak Permainan Mobile Legend terhadap Motivasi Belajar Siswa Sekolah Dasar - Fahmi Rahman Iskandar; Syarip Hidayat; Nana Ganda (Universitas Pendidikan Indonesia Kampus Serang, 2019)
The impact of mobile games now has a major influence on elementary students' learning motivation. The impact varies based on the intensity playing the game. This study aims to determine the impact of the intensity of playing a mobile legend game on the learning motivation of elementary school students in Bayongbong district. This research is a descriptive qualitative study with 10 students with high tendency of playing mobile legend games as research subjects Data was collected through interviews and FGD (forum group discussion) with students’ parents. The results were presented and grouped into three categories based on the intensity of playing time with the impact on learning motivation. The middle category (sometimes playing) resulted by 40% has no impact on learning motivation. The high intensity category (often playing) obtained 40% of respondents and the impact begins to decrease students’ learning motivation. The very high intensity category (always playing) gained 20 % and it make the respondents’ hav no learning motivation. This result showed that the intensity of playing mobile legend game has an impact on elementary school students' learning motivation. Teachers and parents should take this issue as relevant concern to guide their children achive better academic result.